2016
DOI: 10.1007/s12010-016-2158-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Catabolite Regulation of Secondary Metabolite Formation and Morphological Differentiation in Streptomyces coelicolor

Abstract: In the genus Streptomyces, carbon utilization is of significant importance for the expression of genes involved in morphological differentiation and antibiotic production. However, there is little information about the mechanism involved in these effects. In the present work, it was found that glucose exerted a suppressive effect on the Streptomyces coelicolor actinorhodin (Act) and undecylprodigiosin (Red) production, as well as in its morphological differentiation. Accordingly, using a high-density microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Mannitol and glucose exhibited a higher capacity for secondary metabolism when NMMP medium was used and glycerol was shown to have a higher capacity in cases where AM medium was used. Our results also showed that both nutritionally richer media R3 and AM are more suited to germination and the production of secondary metabolites than the minimal NMMP medium, probably due to the presence of Ca 2+ ions (Eaton and Ensign, 1980 ; Lakey et al, 1983 ), L-amino acids (Hirsch and Ensign, 1976b ), or various carbon sources (Romero-Rodriguez et al, 2016 ) in the richer media.…”
Section: Discussionsupporting
confidence: 53%
“…Mannitol and glucose exhibited a higher capacity for secondary metabolism when NMMP medium was used and glycerol was shown to have a higher capacity in cases where AM medium was used. Our results also showed that both nutritionally richer media R3 and AM are more suited to germination and the production of secondary metabolites than the minimal NMMP medium, probably due to the presence of Ca 2+ ions (Eaton and Ensign, 1980 ; Lakey et al, 1983 ), L-amino acids (Hirsch and Ensign, 1976b ), or various carbon sources (Romero-Rodriguez et al, 2016 ) in the richer media.…”
Section: Discussionsupporting
confidence: 53%
“…Firstly, it appears likely that surugamide A biosynthesis may be regulated, at least in part, by carbon catabolite repression (CCR). Carbon catabolite repression is a well-described regulatory mechanism in bacteria that controls carbon metabolism [79,80,81,82], and which has also been reported to regulate the biosynthesis of secondary metabolites in a number of different bacterial species, including in Streptomyces isolates [83,84,85,86]. While the TSB and the YD media contain glucose and dextrins as carbon sources, respectively; the complex polysaccharide starch is the carbon source in the SYP-NaCl medium.…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism is one of the most conserved ones reported in various bacteria, including actinobacteria. It protects the cells against wasting proteinsynthesizing machinery and controls secondary metabolism (Romero-Rodríguez et al, 2016van Der Heul et al, 2018). In Streptomyces, CCR by glucose appears to be due to both carbohydrate metabolism intermediaries like fructose 1,6-bisphosphate or glucose 6-phosphate (Ramos et al, 2004;Borodina et al, 2008) and the enzyme glucose kinase (Glk) (Angell et al, 1994).…”
Section: Crotonylation Of Lysine Residues Of the Glucokinase And Its mentioning
confidence: 99%